Cavernoma cerebeloso complicado con hemorragia asociado a anomalía venosa del desarrollo: reporte de caso - Franco-Chávez, Janina; Chaparro-Franco, Fiorella; Martínez-Chamorro, Alan; Ucedo, Oscar (Medicina Clínica y Social, 2021)
Cerebral cavernoma is a vascular injury of the central nervous system, the second most frequent (10-15%) of the four types of brain malformations, among which are arteriovenous malformation, capillary telangiectasia, and developmental venous anomaly; associating with the last one in approximately 9% of cases. Its estimated prevalence is only 0.4% in the general population. Case report of a 23-year-old woman who came to the emergency department for severe headache, accompanied by severe vertigo and vomiting on several occasions; with altered state of consciousness. A simple computerized axial tomography of the skull was performed. Due to the age of the patient and the location of the injury, a nuclear magnetic resonance was performed, which showed images suggestive of a cerebellar cavernoma complicated with hemorrhage and a contiguous venous angioma. Conservative treatment was performed and a repeat MRI was requested a month after the first indication in order to assess the evolution of the lesion and bleeding. Cavernomas are frequently not detected with angiography due to their slow flow and the tendency to thrombosis, the most sensitive diagnostic tool being nuclear magnetic resonance imaging. Watchful waiting is suggested for multiple injuries, those that are surgically inaccessible or that are uncomplicated.